Peningkatan Digitalisasi Pemasaran dan Pengembangan Produk Rolade Sawi di Kelurahan Tanggung Kota Blitar - Farah Daroin Putri Muzakki; Sumainah Fauziah (Yayasan Daarul Huda Kruengmane, 2023)
Blitar City has considerable potential in the MSME sector to be developed. Each village has its own product characteristics. One example of its product is mustard greens which are in the Kelurahan, especially RW 02 and RW 5. Mustard plants are rich in nutrients that contain antioxidants, so they can maintain heart and digestive health. Processed mustard rolls are a popular dish in Asia, including Indonesia. There are variations of mustard rolls with ingredients such as shrimp or chicken, and served with various sauces. However, these MSMEs have the main obstacle, namely the lack of marketing quality, especially in product branding and marketing. Therefore, students are very enthusiastic about designing activities to maximize in providing assistance to MSME rollade mustard so that they can produce products that have high competitiveness and selling power. With this, it is hoped that the community can manage these superior products well in order to improve the economy and people's welfare.